Respuesta :

[tex]b_1=\frac{2A}{h}-b_2[/tex]

Step-by-step explanation:

Given expression is;

[tex]A=\frac{h(b_1+b_2)}{2}[/tex]

Solving for [tex]b_1[/tex]

Multiplying both sides by 2

[tex]2*A=\frac{h(b_1+b_2)}{2}*2\\2A=h(b_1+b_2)[/tex]

Dividing both sides by h

[tex]\frac{2A}{h}=\frac{h(b_1+b_2)}{h}\\\frac{2A}{h}=b_1+b_2[/tex]

Subtracting [tex]b_2[/tex] from both sides

[tex]\frac{2A}{h}-b_2=b_1+b_2-b_2\\\frac{2A}{h}-b_2=b_1\\b_1=\frac{2A}{h}-b_2[/tex]

[tex]b_1=\frac{2A}{h}-b_2[/tex]

Keywords: division, subtraction

Learn more about subtraction at:

  • brainly.com/question/11145277
  • brainly.com/question/11150876

#LearnwithBrainly

ACCESS MORE